Avrupa İnsan Hakları Sözleşmesi çerçevesinde sanatsal ifade özgürlüğü - Yünlüel, Reha (My University, 2023)
İki bölümden oluşan tezimizin ilk bölümünde; sanatsal ifade özgürlüğünü “yaratı”, “düşünce” ve “ifade” üzerinden tanımlayarak “insan hakları”nın olası temellerine mercek tutmaya çalıştık. İkinci bölümünde ise, bir ürün olarak “sanatsal ifade”ye yöneltilen müdahaleler üzerinden önce, kişiliği ile dolaşım hakkının üzerinde durduk; sonrasında da “diğerlerinin hakları” ile sürtüşme noktalarını Avrupa İnsan Hakları Mahkemesinin “sanatsal ifade özgürlüğü”ne ilişkin kararları üzerinden göstermeye çalıştık. Tezlerimizden birisini oluşturan “sürtüşme noktaları” yalnızca “sanatsal ifade özgürlüğü” açısından değil ama tüm özgürlükler açısından bir tasnifat olanağı sunmaktadır. Bunlar: “küçüklerin güvenliği”, “manevi değerlerin güvenliği”, “genelin güvenliği” ile “öznel’in güvenliği”dir Netice olarak geldiğimiz noktanın, Avrupa İnsan Hakları Sözleşmesi Çerçevesinde Sanatsal İfade Özgürlüğü’nden çok Sanatsal İfade Özgürlüğü Karşısında Avrupa İnsan Hakları Sözleşmesi olduğu söylenebilecektir. Nitekim temel bir hak ve özgürlüğün teminat altına alınması, o hakkın varlığını, teminat altına alındığı andan başlatmaz. Hele de Avrupa İnsan Hakları Sözleşmesi’nin asli koruma aracı olmaktan çok ikincil bir koruma aracı olduğu göz önünde olduğu düşünüldüğünde.

In the first part of our thesis, which consists of two parts, we tried to focus on the potential foundations of “human rights” by defining artistic freedom of expression through “creation”, “thought” and “expression”. In the second part we looked at the interventions directed at “artistic expression” as a product, and first focused on its personality and the right of circulation; then we tried to show the friction points with “the rights of others” through the decisions of the European Court of Human Rights on “freedom of artistic expression”. The term friction points, being one of our theses, offers a classification opportunity not only in terms of freedom of artistic expression but also in terms of all freedoms. These are: security of minors, security of moral values, security of the general and security of the subjective. As a result, it can be said that the point we have reached is the European Convention on Human Rights versus Freedom of Artistic Expression rather than Freedom of Artistic Expression within the Framework of the European Convention on Human Rights. As a matter of fact, securing a fundamental right and freedom does not start from the moment when the existence of that right it is secured. Especially considering that the European Convention on Human Rights is a secondary protection tool rather than a primary protection tool.
Keywords: Freedom and art; Freedom of artistic expression; Freedom of expression; Freedom of speech; Human rights; İfade özgürlüğü; İnsan hakları; Özgürlük ve sanat; Sanatsal ifade özgürlüğü